Solution
- The function given is:
![f(x)=2^(x+1)-3](https://img.qammunity.org/2023/formulas/mathematics/college/nfo04ap8syl4jzw4af1tgnowhr604okkyu.png)
- The best way to understand the solution is to plot the function.
- The plot of the function is given below:
- From the above, we can already make the following deductions depicted below:
- Thus, we can answer the questions asked as follows:
Growth or Decay:
- This is clearly a GROWTH function as it increases from left to right.
- The reason for this increase is the term
![2^(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/uy6h1ztujlyrq5eokapqryor0nvzx418jo.png)
- 2 is the rate of change and since it is greater than 1, the function is increasing. If it were less than 1, it would be decay.
Domain:
- The domain is the set of all x-values for which the function is defined. The function has no breaks from left to right, thus, we can conclude that the domain is
![Domain:(-\infty,\infty)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vmqw7x55ekv0wqwih8n4kz5upa5hlpfwl4.png)
Range:
- The range is the set of all y-values for which the function is defined. The function has a minimum value of -3, which is also the Horizontal asymptote of the function. This is because,
![\begin{gathered} \text{ For any exponential function} \\ f(x)=ab^x+c \\ c\text{ is the horizontal asymptote of the function and the minimum value of the function} \\ \\ \text{ Also, if we substitute }x=-\infty\text{ into the function give,} \\ f(x)=2^(-\infty+1)-3 \\ f(x)=(1)/(2^(\infty))-3=0-3=-3 \\ \\ \text{ Thus, when we move further and further towards the left of the graph, the value of} \\ \text{ f\lparen x\rparen becomes -3, just as we established earlier} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/az6w8t71ttdqpgu9ik81ch00w5flrzttn3.png)
Y-intercept:
- The y-intercept is simply where the graph crosses the y-axis. This also happens to be where x = 0 in the graph as well.
- From the figure above, we have that the y-intercept is (0, -1)
- But we can also get it from the equation by substituting the value of x = 0 into the function
![\begin{gathered} f(x)=2^(x+1)-3 \\ \text{ put }x=0 \\ f(x)=2^(0+1)-3 \\ f(x)=2-3 \\ f(x)=-1 \\ \text{ Thus, when }x=0,f(x)=-1 \\ \\ \text{ Thus, the y-intercept is }(0,-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j9n1y8ln4jzcdjhgvrpjv2esdh6gqvg25x.png)
Increasing Interval and Decreasing Interval:
- The interval for which the function is increasing is done by testing values of x and checking out the trend of the function. Usually, we test a negative value, x = 0, a positive value, then, negative and positive infinity.
- But since we have the graph plotted above, we can easily see that the graph is ALWAYS INCREASING over the interval
![x\in(-\infty,\infty)](https://img.qammunity.org/2023/formulas/mathematics/college/2obwcs64b928vvvux8dtw6v0lghkmo0ajz.png)
End behavior:
- The end behavior of the graph is simply the values of y as x tends to negative and positive infinity.
- Thus, we have:
![\begin{gathered} f(x)=2^(x+1)-3 \\ \text{ Put }x=-\infty, \\ f(-\infty)=2^(-\infty+1)-3 \\ f(-\infty)=-3 \\ \\ \text{ Put }x=\infty \\ f(\infty)=2^(\infty+1)-3 \\ f(\infty)=\infty-3 \\ f(\infty)=\infty \\ \\ \text{ Thus, the End behavior of the function is:} \\ As\text{ }x\to\infty,f(x)\to\infty \\ As\text{ }x\to-\infty,f(x)\to-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a1gan4x6hne0q2iwc0b9r4u07xiuc1vbwt.png)